2005
DOI: 10.1111/j.1600-0404.2005.00517.x
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-TRODAT-1 SPECT study in early Parkinson's disease and essential tremor

Abstract: 99mTc-TRODAT-1 SPECT can detect the dysfunction of nigrostriatal system in patients with early PD and provided a feasible tool to help differentiate early PD from ET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The reduced dopaminergic uptake pattern differed between the studies. Alternatively, the majority of DAT-SPECT and DOPA-PET studies did not show any deviations in striatal uptake in a total of 168 essential tremor patients (Brooks et al, 1992; Breit et al, 2006; Antonini et al, 2001; Doepp et al, 2008; Wang et al, 2005; Asenbaum et al, 1998; Benamer et al, 2000; Di et al, 2012; Isaias et al, 2010; Roselli et al, 2010; Parkinson study group, 2000). The two largest amongst these studies, with groups of 27 and 32 essential tremor patients, included patients fulfilling the clinical criteria and without any signs of parkinsonism (Asenbaum et al, 1998; Benamer et al, 2000).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The reduced dopaminergic uptake pattern differed between the studies. Alternatively, the majority of DAT-SPECT and DOPA-PET studies did not show any deviations in striatal uptake in a total of 168 essential tremor patients (Brooks et al, 1992; Breit et al, 2006; Antonini et al, 2001; Doepp et al, 2008; Wang et al, 2005; Asenbaum et al, 1998; Benamer et al, 2000; Di et al, 2012; Isaias et al, 2010; Roselli et al, 2010; Parkinson study group, 2000). The two largest amongst these studies, with groups of 27 and 32 essential tremor patients, included patients fulfilling the clinical criteria and without any signs of parkinsonism (Asenbaum et al, 1998; Benamer et al, 2000).…”
Section: Resultsmentioning
confidence: 95%
“…Most scintigraphic studies looking into the basal ganglia found no dopaminergic deficits in essential tremor (Antonini et al, 2001; Asenbaum et al, 1998; Benamer et al, 2000; Breit et al, 2006; Brooks et al, 1992; Doepp et al, 2008; Isaias and Antonini, 2010; Wang et al, 2005) while two studies measured slight abnormalities (Gerasimou et al, 2012; Isaias et al, 2008). One study reported iron accumulation in the basal ganglia (Novellino et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…6 In addition to FP-CIT, the availability of DAT binding sites can also be measured with other tracers, such as iodine-123-beta-carbomethoxy-3 beta-(4-iodophenyltropane) (b)CIT or [99mTc]TRODAT-1. [7][8][9][10][11][12] To analyze DAT-SPECT images three different methods are available, that is, the visual assessment, the region of interest (ROI) approach, and the voxel-based analysis. We summarize the characteristics of the named methods to analyze DAT-SPECT images and review their potential for various clinical and experimental indications.…”
mentioning
confidence: 99%
“…Studies of ( 99m Tc)‐TRODAT‐1 have also shown significantly reduced striatal uptake in PD compared to non‐degenerative causes of Parkinsonism, such as essential tremor, vascular Parkinsonism and drug‐induced Parkinsonism . However, PD cannot be reliably distinguished from atypical Parkinsonian syndromes (which are also characterised by dopaminergic degeneration), such as multiple system atrophy, corticobasal degeneration and progressive supranuclear palsy .…”
Section: Discussionmentioning
confidence: 99%